Granulomatous mastitis in a male breast: A case report and review of literature - Kei Kawashima; Shinya Yamamoto; Kazutaka Narui; Yoshie Fujiwara; Shoko Adachi; Mahato Sasamoto; Masanori Oshi; Akimitsu Yamada; Eita Kumagai; Masako Otani; Itaru Endo (Clinical Case Reports, 2023)
Abstract Granulomatous mastitis (GM) is a rare disease, particularly among men. Herein, we present a case of GM diagnosed in a 63‐year‐old male patient who showed reduction in the tumor size during 3 months of observation.